Religious Moderation In Slogans, Practices, and Madrasah Reflection - Maspeke , Fithriyah (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
The lack of understanding of madrasah students about the concept of religious moderation and the lack of encounters between religions in society is the main basis for this research literature study. Religious moderation is a discourse as well as a practice needed in a multicultural society such as in North Sulawesi. This means that where there is diversity, that is where the value of moderation must be present and become the lifeblood of the link between members of the community. The results of the study indicate that there are solutions that can be implemented in strengthening religious moderation, including creating or using existing mottos in society as a basis for instilling religious moderation values, such as the mottos of torang samua basudara and torang samua created by God in North Sulawesi. Building houses of worship side by side, of course, can open meeting spaces and increase the intensity of encounters between religions as the main capital in strengthening religious moderation. In madrasas, madrasas can make madrasah moderation days and hold interfaith student exchanges so that religious moderation is familiar among madrasah students who are part of the millennial generation. Then, you can also make a religious moderation accompanying diploma as a sign of the maturity of student religious moderation which is oriented towards attitudes and moderation schools as an alternative to strengthening community religious moderation, especially the millennial generation.